2011
DOI: 10.1039/c1sm05128h
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication in soft rough contacts: A novel homogenized approach. Part I - Theory

Abstract: We study the lubricated steady sliding contact between rough surfaces of (elastically) soft solids. A novel mean field theory of mixed lubrication is presented, which takes into account the coupled effect of asperity-asperity and asperity-fluid interactions. We calculate the fluid flow factors, and discuss the nature of the transition from the boundary lubrication regime, where the normal load is supported by the asperity-asperity interactions (sometimes mediated by boundary films), to the hydrodynamic regime,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Contact mechanics between rough surfaces plays a crucial role in a large number of engineering applications, ranging from seals [1,2], boundary and mixed lubrication [3,4], adhesive systems and friction [5][6][7]. Recently, an increasing interest in these topics has been motivated by the increasing efforts made to face up new technological challenges, such as the manufacturing of novel bio-inspired adhesives [8][9][10], the optimization of seals [11,12], the extreme downsizing of mechanical and electrical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Contact mechanics between rough surfaces plays a crucial role in a large number of engineering applications, ranging from seals [1,2], boundary and mixed lubrication [3,4], adhesive systems and friction [5][6][7]. Recently, an increasing interest in these topics has been motivated by the increasing efforts made to face up new technological challenges, such as the manufacturing of novel bio-inspired adhesives [8][9][10], the optimization of seals [11,12], the extreme downsizing of mechanical and electrical devices.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for such a behavior has been recently proposed in Refs. [18] and [19], where the authors showed that, at least in terms of asperities flattening, the strength of the fluid-asperity interactions is maximum for the transverse roughness, i.e. when the roughness grooves are aligned perpendicularly to the sliding direction (see also [20]- [24]).…”
Section: The Effect Of Micro-ehl Contacts On the Macroscopic Con-mentioning
confidence: 99%
“…However, to the best of authors' knowledge, the role played by the roughness anisotropy on the solid contact and lubricant dynamics at the interface of soft contacts has not been investigated yet. In this paper we focus on the experimental investigation of the effects of roughness anisotropy on the soft mixed lubrication and make use of recent theoretical and numerical developments [18]- [24] to, at least qualitatively, explain the behavior observed in our experimental investigations. Our setup consists of a metal ball in a steady-sliding contact with a fixed (anisotropically) rough PDMS substrate, see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we will show how the theory can be extended to also predict the distribution of interfacial separations P (u). This quantity is of crucial importance for problems like leak-rate of seals Lorenz & Persson, 2010a,b) or mixed lubrication (Persson, 2010;Scaraggi et al, 2011;Lorenz & Persson, 2010c). The analytical results will be compared to numerical solutions obtained using (a) a half-space method based on the Boussinesq equation (BEM), (b) a Green's function molecular dynamics technique and (c) smart-block molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%